2021
DOI: 10.1093/ibd/izaa347.085
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Personalized Model of Intestinal Fibrosis Using Human Intestinal Organoids Derived From Induced Pluripotent Stem Cells

Abstract: Background Intestinal fibrosis is a serious complication of inflammatory bowel disease (IBD) with > 20% of Crohn’s disease patients developing this complication within 10 years of diagnosis. Despite improvements in anti-inflammatory medication, its incidence remains stubbornly high and thus far surgical intervention remains the only treatment option. Numerous cell types including intestinal epithelial and mesenchymal cells are implicated in this process, yet studies are hampered by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The pathogenesis of CD fibrosis is not completely understood, which is largely due to the lack of human-specific intestinal fibrosis models. Excitingly, in 2021, Estrada et al 10 generated human intestinal organoids (HIOs) using induced pluripotent stem cells from CD patients with strictures, and epithelial and mesenchymal cells derived from HIOs under the stimulation of transforming growth factor beta (TGF-β) were able to replicate intestinal fibrotic responses. This model shed new insight on the exploration of mechanisms underlying intestinal fibrosis.…”
Section: Mechanism Of Intestinal Stricturesmentioning
confidence: 99%
“…The pathogenesis of CD fibrosis is not completely understood, which is largely due to the lack of human-specific intestinal fibrosis models. Excitingly, in 2021, Estrada et al 10 generated human intestinal organoids (HIOs) using induced pluripotent stem cells from CD patients with strictures, and epithelial and mesenchymal cells derived from HIOs under the stimulation of transforming growth factor beta (TGF-β) were able to replicate intestinal fibrotic responses. This model shed new insight on the exploration of mechanisms underlying intestinal fibrosis.…”
Section: Mechanism Of Intestinal Stricturesmentioning
confidence: 99%
“…Abnormal fibrotic deposition of ECM proteins and myofibroblast activation were observed when Duchenne muscular dystrophy (DMD) fibroblasts were embedded in the 3D vascularized muscle environment ( Bersini et al, 2018 ) ( Table 1 ). Estrada et al (2021) reported the generation of human intestinal organoids derived from patient derived-induced pluripotent stem cells. These 3D organoids provided a personalized approach for modeling intestinal fibrotic responses in vitro ( Table 1 ).…”
Section: Engineered Models For Studying Human Fibrotic Diseasesmentioning
confidence: 99%
“…Human iPSCs are self-renewing pluripotent cells that can produce cells from any of the three germ layers (endoderm, ectoderm, and mesoderm) 186,188 . Human iPSCs can be differentiated down the intestinal epithelial lineage and used to grow human intestinal organoids (HIOs) 189 , which have been used extensively to study IBD 190,191 , host-microbe interactions 189,192 , and, more recently, as a method to develop CFTR modulator therapies 193 .…”
Section: Future Studiesmentioning
confidence: 99%